Changes in polyamine content and localization of Pinus sylvestris ADC and Suillus variegatus ODC mRNA transcripts during the formation of mycorrhizal interaction in an in vitro cultivation system - Niemi, Karoliina (Journal of experimental botany, 2006)
The involvement of polyamines (PAs) in the interaction between Pinus sylvestris L. seedlings and an ectomycorrhizal fungus Suillus variegatus (Swatz: Fr.) O. Kunze was studied in an in vitro cultivation system. PA concentrations in seedlings were analysed after 1, 3, and 5 weeks in dual culture with S. variegatus, and changes in PA pools were compared with the growth of the seedlings. Pinus sylvestris arginine decarboxylase (ADC) and S. variegatus ornithine decarboxylase (ODC) mRNA transcripts were localized during the formation of mycorrhizas. During mycorrhiza formation, Suillus variegatus ODC transcripts were found in developing hyphal mantle and Hartig net, and P. sylvestris ADC transcripts in specific root parenchyma cells adjacent to tracheids and in mitotic cells of the root apical meristem. However, no unambiguous difference in ADC transcript localization between inoculated and non-inoculated roots was observed. Regardless of the unchanged distribution of ADC transcripts, inoculation with S. variegatus increased free putrescine, spermidine, and spermine concentrations in roots within the first week in dual culture. The concentration of free and conjugated putrescine and conjugated spermidine also increased in the needles due to the fungus. The fungus-induced lateral root formation and main root elongation were greatest between the first and third week in dual culture, coinciding with retarded accumulation or a decrease of free PAs. These results show that accumulation of PAs in the host plant is one of the first indicators of the establishment of ectomycorrhizal interaction between P. sylvestris and S. variegatus in the in vitro system